PENGARUH SALES PROMOSION DAN PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN PADA UD. CIPTA KARYA ABADI LAMONGAN - Rahayu Mufiyati; Nawari Nawari (LPPM UNISDA, 2020)
UD. Cipta Karya abadi is a company engaged in trading household appliances. Its flagship product is the multipurpose pot CKA POT. Using special and unique concepts in the sales activities of superior products, namely by direct sales, by conducting promotions, introducing products and even directly practicing cooking demonstrations in front of prospective customers. The purpose of this research is to find out the effect of Sales Promotion and Personal Selling partially or simultaneously on Purchasing Decisions. The number of samples in this study were 98 respondents. While the sampling technique used in this study was simple random sampling technique. The data is analyzed using the SPSS program, Variable Sales Risk (X1) = 0,000 <0,05, Personal Selling Variable (X2) = 0,000 <0,05. From the equation above the variable significance of the price is smaller than 0.05, the significance of the Sales Promosion variable is smaller than 0.005 and the significance of the small Personal Selling variable is greater than 0.05, then the X1 variable has a positive effect on Y and X2 has a positive effect on variable Y.